English Literature Study Program Students' Mindset of Grammar Usage and Mistake - Sembiring, Lina Tri Astuty Beru; Sembiring, Silvia; Awal, Nurul Septi Adianti; Sangian, Engga Zakaria (Journal Of Dehasen Educational Review, 2020)
Writing is considered the most complex skill to master not only requiring good vocabulary but also grammar. This research is aimed to analyze students' grammatical errors in writing, especially in descriptive text. In addition, (Wati & Nursyaebah, 2017) there are six classifications of grammatical errors; they are verb agreement (Leech, 1985), use of capitalization (Oshima, 1988), sentence patterns (Ross, 1975) pronouns and spelling (Brooks, 1964). The data were analyzed based on the analysis of students' errors in writing. The research findings show that most students make mistakes in agreeing verbs 41% caused by the wrong use of the simple present, followed by pronouns 18%, usage 15%, sentence patterns 12%, spelling 9%, and capitalization errors 5%. From the findings, it is necessary or students learn more about English grammar and it is suggested for teachers to teach again about verb and pronoun agreement as the most failure that most students do in their writing. Keyword: Grammatical Errors, Writing, Descriptive Text